2020
DOI: 10.3389/fvets.2020.584948
|View full text |Cite
|
Sign up to set email alerts
|

Protein Cargo of Extracellular Vesicles From Bovine Follicular Fluid and Analysis of Their Origin From Different Ovarian Cells

Abstract: Follicular fluid (FF) fills the interior portion of the ovarian antral follicle and provides a suitable microenvironment for the growth of the enclosed oocyte through molecular factors that originate from plasma and the secretions of follicular cells. FF contains extracellular nanovesicles (ffEVs), including 30–100-nm membrane-coated exosomes, which carry different types of RNA, proteins, and lipids and directly influence oocyte competence to develop embryo. In the present study, we aimed to characterize the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 76 publications
(153 reference statements)
0
23
0
6
Order By: Relevance
“…Nordin et al, [ 38 ] have shown that UC can induce some EV disruption after UC for 70 min at 120,000 g and recommended that the recovery of intact EVs by UC should be done at a maximum speed of 100,000× g . In our laboratory, we have used UC protocols based on 100,000× g for this study, and also in previous studies to isolate oviductal and follicular EVs from different species with good results based on TEM observations [ 15 , 16 , 17 , 51 , 52 , 53 ]. However, considering the possibility that UC or CE processes could affect the EVs morphology, we used trehalose during the CE wash and dissolved the pellet after UC in PBS/25 mM trehalose.…”
Section: Discussionmentioning
confidence: 99%
“…Nordin et al, [ 38 ] have shown that UC can induce some EV disruption after UC for 70 min at 120,000 g and recommended that the recovery of intact EVs by UC should be done at a maximum speed of 100,000× g . In our laboratory, we have used UC protocols based on 100,000× g for this study, and also in previous studies to isolate oviductal and follicular EVs from different species with good results based on TEM observations [ 15 , 16 , 17 , 51 , 52 , 53 ]. However, considering the possibility that UC or CE processes could affect the EVs morphology, we used trehalose during the CE wash and dissolved the pellet after UC in PBS/25 mM trehalose.…”
Section: Discussionmentioning
confidence: 99%
“…We then compared the lists of the proteins identified from bovine follicular fluid exosome-like EVs (294 IDs) [ 45 ], cumulus cells (1381 IDs) [ 52 ], granulosa cells (418 IDs) [ 45 ], and bovine oocytes (1936 protein IDs) [ 53 ] with the list of follicular palmitoyl-proteins ( Figure 2 a). 32 IDs, 48 IDs and 43 IDs of follicular palmitoy-proteins were shared with GC, CC and oocyte proteomes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate expression of palmitoylation and depalmitoylation enzymes in bovine follicular cells and oocytes, we have compared the list of 41 known enzymes with the lists of proteins identified from bovine oocytes [ 53 ], cumulus cells [ 52 , 56 ], mural GC, and extracellular exosome-like EVs from follicular fluid [ 45 ]. Indeed, LYPLA1 and PPT2 were found among 593 proteins identified in bovine GC [ 45 ]; PPT1, PPT2 and LYPLA2 were found among 2018 proteins identified in bovine oocytes [ 53 ], and PPT1, LYPLA1 and LYPLA2 proteins were reported in the list of 1703 identified proteins from CC surrounding immature oocytes [ 52 ]. PPT1 and LYPLA2 were also identified from CC surrounding in vivo and in vitro mature oocytes [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations